D.D.C Implementation of D.D.C controller for Rationalize the consumption of electrical energy Case study (Hotel & Mall) (Damascus University Journal for engineering sciences, 2023)
It is no longer a secret to anyone, the global trend prevailing towards both reducing the electrical power consumption's excess and controlling that consumption especially in buildings and facilities. All of the automation, control, and data acquisition playing the main role of that trends and that what is known as buildings management systems in  (BMS). Particularly with regard to HVAC's loads in huge projects with higher HVAC's systems consumption researchers worldwide are focusing on developing a set of intelligent systems and programmable controller  that enhance the consumption reduction concept.This article study evaluate the using of DDC in a case study of a massive installations consisting of a hotel and a shopping Mall with a total floor area of approximate 8200 m2, where HVAC represents the biggest value of all loads. A Building Management  process was applied to the HVAC's Loads especially and the rest of loads generally  including explaining the DDC programming stages and mechanism, shows the results of this system and identify the savings achieved by the BMS system the using the DDC in the studied building.
Keywords: HVAC; DDC; BMS; Controller